Велике розселення слов’ян - Баран, В.Д. (Археологія, 1998)
Стаття розкриває процеси великого розселення слов'ян, що стало основою іх етномовної диференціації та формування зародків усіх сучасних слов'янських народів. Процессы великого расселения славян в середине I тыс. необходимо оценивать не только с позиций освоения ими новых территорий и славянизации субстратного населения. Продвигаясь на север и северо-восток, на юг и запад, уже в то время разные славянские племенные группы смешивались с неславянским населением и вместе формировали новые этнические образования, относительно их славянских племенных союзов, что остались на исторической прародине. В статье доказывается, что эпоха великого расселения славян одновременно является эпохой зарождения трех восточнославянских этносов: белорусского, русского и украинского, как и юго-западнославянских народов. Киевское государство во главе с династией Рюриковичей не остановило, а лишь замедлило процессы формирования трех частей западного славянства, начало которых совпадает с эпохой великого переселения народов. Разгром монголо-татарами уже разных в то время (XII—XIII вв.) самостоятельных княжеств восточного славянства, попавших в состав разных государств, не начал, а лишь усилил и привел к завершению процессы восточнославянского народообразования. Processes of the great dispersion of the Slavs in the middle of the 1st millennium should be analyzed not only from the standpoint of assimilation of new territories and slavification of the substrate population. Moving to the north and north-east, to the south and to the west different groups of Slavic tribes by that moment mixed up with non-Slavic population formed new ethnic groups with respect to those which remained in their historical pra-motherland. It is proved that the epoch of the great dispersion of the Slavs is simultaneously the period of the birth of three east-Slavic ethnic groups: Byelorussian, Russian, and Ukrainian peoples, as well as of south-west-Slavic peoples. The Kyiv state headed by the dynasty of the Ryurikovichi did not halt but only made somewhat slower the processes of formation of three parts of east-Slavic peoples; the onset of those processes comes back to the epoch of the great migration of peoples. Different and independent at that time (the 12th — 13th cent.) principalities of the east Slavs which found themselves within different states were crushed by the Mongols-Tatars. That defeat did not give rise to, but only intensified and led to the completion processes of the East-Slavic peoples’ formation.